STAT3 Silencing and TLR7/8 Pathway Activation Repolarize and Suppress Myeloid-Derived Suppressor Cells From Breast Cancer Patients - Safarzadeh, Elham; Mohammadi, Ali; Mansoori, Behzad; Duijf, Pascal H. G.; Hashemzadeh, Shahryar; Khaze, Vahid; Kazemi, Tohid; Derakhshani, Afshin; Silvestris, Nicola; Baradaran, Behzad (Frontiers in Immunology, 2021)
Cancer cells escape immune destruction. Critical in this regard are myeloid-derived suppressor cells (MDSCs), which are immunosuppressive in various cancers, including breast cancer (BC). However, the precise mechanisms are unknown.We isolated and immunophenotyped HLA-DR-CD33+ MDSCs and CD3+ T cells from peripheral blood of BC patients and healthy donors using flow cytometry. Transfection of short-interfering RNAs and treatment with a TLR7/8 agonist altered pathway activities in vitro. Gene expression was analyzed using qRT-PCR, western blotting and immunohistochemistry.Our findings showed that there is an association betweenthe progression of BCand increased levels of circulating HLA-DR-CD33+ MDSCs. These cells strongly suppress both autologous and analogous CD3+ T cell proliferation and enter the tumor microenvironment. We also identifiedincreased STAT3 signaling and increased IDO and IL-10 expression in BC-derived MDSCs as mechanisms of immunosuppression. Further, STAT3 inhibition and TLR7/8 pathway stimulation reduce the immunosuppressive activity of patient-derived MDSCs on T cells by inducing MDSC repolarization and differentiation into mature myeloid cells. This also alters the expression of critical cytokines and transcription factors in CD3+ T cells and, importantly, reduces the proliferation of breast cancer cells. Finally, while chemotherapy is able to significantly reduce circulating MDSCs’ level in patients with breast cancer, these MDSCs remained highly T cell-suppressive.We identified a novel molecular mechanism of MDSC-mediated immunosuppression. STAT3 inhibition and TLR7/8 pathway stimulation in MDSCs repolarize and suppress MDSCs from breast cancer patients. This offers new opportunities for BC immunotherapy.